Mitigation priorities in the agricultural sector of some caribbean nationsTT - Priorités de réduction dans le secteur de l'agriculture de quelques nations caraïbes. - Gob, Rosaire (1968-...) (Institut national de la recherche agronomique (France). Centre de recherches, 2016)
In this study, Greenhouse Gas Emission Profiles (GHGE) in the agricultural sector of some Caribbean countries are examined and the proposed strategies to mitigate climate change are assessed. While Caribbean countries have extremely low emissions compared to most other countries, relative to human population, area and agricultural production, values in the region are comparable to the rest of the world, including some of the most populous and largest countries. Out of eight countries, only Guyana, Guadeloupe and Puerto Rico have documented any significant intention to mitigate GHGs. Emissions versus production can be useful to better understand where mitigation should be prioritized. These measures are more likely to improve food security goals and contribute to climate change adaptation.